The Importance of Detailed Audio-Vestibular Monitoring in Familial Non-Syndromic Hearing Losses: A Longitudinal Study - Burak Kabiş; Nuriye Yıldırım Gökay (Gazi Medical Journal)
Objective: This study aimed to evaluate the audiological and vestibular findings of two family members with progressive sensorineural-type hearing loss at high frequencies according to age. Methods: Pure tone audiometry, speech audiometry, and immittancemetry tests were performed for audiological evaluation of the two families participating in the study. A total of 11 volunteers were included: the mother, father, and three children from the first family; and the mother-father and four children from the second family. A videonystagmography was performed to rule out neurological diseases. A computerized dynamic posturography (CDP) was performed to evaluate postural control. Audiovestibular findings were recorded by year and analyzed using SPSS v.24. program. Results: Sensorineural-type hearing loss, which was evident at high frequencies, was detected in all family members. A significant progressive deterioration was observed in the hearing thresholds of family members and in the CDP results over the years. Conclusion: This study revealed that audiovestibular follow-up is essential for genetic hearing loss. The findings demonstrated the importance of follow-up and genetic counseling in terms of progressive hearing loss, even when newborns undergo hearing screening.